Biology of the oriental bamboo-inhabiting fly felderimyia gombakensis and observations on mating trophallaxis in felderimyia (Insecta, Diptera, Tephritidae, Phytalmiinae, Acanthonevrini) - Hashim, Rosli; Freidberg, A.; Dohm, P.; Kovač, D. (2008)
Biology of the three known species of Felderimyia (F. gombakensis, F. fuscipennis and F. flavipennis), all South-East Asian and associated with bamboo, was studied with emphasis on F. gombakensis. In F. gombakensis oviposition takes place on the taller shoots (2 m and higher) of several bamboo species. The eggs are inserted under the edge of the culm sheaths. The freshly hatched larvae crawl into the water-filled internode cavities through holes made by the larvae of leaf beetles of the genus Lasiochila (Coleoptera, Chrysomelidae, Hispinae). The F. gombakensis larvae develop in the water or in the semi-aquatic zone above the water surface. They feed on organic matter scraped from the interior bamboo wall. During courtship males of all Felderimyia species produce a nuptial gift made of a white viscous secretion, which is deposited on the surface of a bamboo culm and eaten by the female prior to, during and often also after copulation. Furthermore, we present new collection records for F. gombakensis (Thailand, South China) and F. fuscipennis (Southwest India). © E. Schweizerbart'sche Verlagsbuchhandlung (Nägele u. Obermiller), 2008.